2021
DOI: 10.1021/acsnano.0c08349
|View full text |Cite
|
Sign up to set email alerts
|

Quo Vadis, Nanoparticle-Enabled In Vivo Fluorescence Imaging?

Abstract: The exciting advancements that we are currently witnessing in terms of novel materials and synthesis approaches are leading to the development of colloidal nanoparticles (NPs) with increasingly greater tunable properties. We have now reached a point where it is possible to synthesize colloidal NPs with functionalities tailored to specific societal demands. The impact of this new wave of colloidal NPs has been especially important in the field of biomedicine. In that vein, luminescent NPs with improved brightne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 255 publications
(470 reference statements)
0
32
0
Order By: Relevance
“…Remote temperature sensing with noninvasive optical methods becomes increasingly popular. [ 1–4 ] Potential application areas range from biothermal imaging, [ 5,6 ] temperature monitoring in catalysis, [ 7–10 ] microelectronics, [ 11 ] or molecular logics [ 12 ] to the investigation of fundamental thermodynamic phenomena [ 13 ] at the micro‐ and nanoscale. One of the conceptually simplest ways of optical temperature sensing, also in terms of the required setup, is the exploitation of the luminescence intensity ratio (LIR) of two emission bands due to radiative transitions from two thermally coupled excited levels of an ensemble of non‐interacting ions.…”
Section: Introductionmentioning
confidence: 99%
“…Remote temperature sensing with noninvasive optical methods becomes increasingly popular. [ 1–4 ] Potential application areas range from biothermal imaging, [ 5,6 ] temperature monitoring in catalysis, [ 7–10 ] microelectronics, [ 11 ] or molecular logics [ 12 ] to the investigation of fundamental thermodynamic phenomena [ 13 ] at the micro‐ and nanoscale. One of the conceptually simplest ways of optical temperature sensing, also in terms of the required setup, is the exploitation of the luminescence intensity ratio (LIR) of two emission bands due to radiative transitions from two thermally coupled excited levels of an ensemble of non‐interacting ions.…”
Section: Introductionmentioning
confidence: 99%
“… 5 7 Furthermore, for NPs to be effectively translated to the clinic, fundamental studies of their photochemical properties must be complimented with research on their biological behavior and cytotoxicity. 3 , 7 10 …”
Section: Introductionmentioning
confidence: 99%
“…These nanomaterials differ in size, shape, composition, and function; thus, rationally engineered NPs act as probes for biosensing, optical imaging, therapy, and nanoscale thermometry, to name a few. In the context of in vitro / in vivo use of NPs, successful NP entry into the cell and accumulation of NPs at the targeted site becomes vital. It is imperative to have knowledge of the NP behavior in a biological environment, interaction with cells, as well as the fate of the NPs once inside the cell. Furthermore, for NPs to be effectively translated to the clinic, fundamental studies of their photochemical properties must be complimented with research on their biological behavior and cytotoxicity. , …”
Section: Introductionmentioning
confidence: 99%
“…Such conditions are particularly relevant for biomedical applications where, to avoid damage, the excitation power density needs to stay below specific safety levels. Moreover, photon extinction by biological tissues strongly reduces both the number of excitation photons reaching the luminescent probe (nanoparticle) and the number of emitted photons collected by the detection systems 41 . Swieten et al have demonstrated that when working in conditions of low signal-to-noise ratio, the thermal uncertainty is affected and the performance of the thermometer is compromised 42 .…”
Section: Resultsmentioning
confidence: 99%